The Influence of Parenting and Social Environment on Bullying - Jaya, Wiwik Hidayati; Alam, Muhammad Syahrul; Masyhuri, Robertus; Idelriani, Idelriani (An Idea Nursing Journal, 2024)
Adolescence is a transitional age from childhood to adulthood, a process of development and search for identity. The research aimed to identify parenting patterns and the social environment on bullying behavior in teenagers at Hasanuddin Gowa High School and to analyze the influence of parenting patterns and the social environment on bullying behavior. The research design used was analytical with a Cross- Sectional Study approach. The research results were obtained using a questionnaire sheet with a sample size of 52 respondents. Sampling was taken purposively. The results of the bivariate analysis show that there is an influence of parental parenting on bullying behavior using the multiple linear regression test with the t-test, the calculated t value > t table (2.703 > 1.677) and a significant value of 0.001 < 0.05 and the social environment on bullying behavior obtained using the t-test. Calculated t value > t table (2.561 > 1.677) and significant value 0.000 < 0.05, this research concludes that there is an influence between parental parenting patterns on bullying behavior and the social environment on bullying behavior at Hasanuddin Gowa High School. It is recommended that schools can further improve education regarding the impact of bullying behavior which has recently become a severe problem in the education sector. The school must also constantly monitor and control any negative student behavior so that it does not have a worse impact in the future.